An investigation of the potential role for environmental education in the conservation of the Swartkops estuary and Swartkops Nature Reserve - Kitson, Brian Anthony Austen (Rhodes University, Faculty of Education, Department of Education, 1994)
This study explores the potential role of an environmental education approach towards the conservation of the Swartkops Estuary and Swartkops Nature Reserve. More specifically it examines the opinions, feelings and perceptions of a sample of twenty seven people, who have a vested interest, in the possible conservation of the area. These stakeholders were comprised of people representing all the various groups and communities that use either or both the estuary and reserve. Opinions were examined by means of a qualitative data analysis from semi-structured interviews. The conservation opinions of respondents were obtained on both general topics and more detailed areas. Due to the small sample and exploratory nature of the project, these results should be viewed as tentative. Proposals are made for increasing the impact of Environmental Education programmes in this and similar environments, and recommendations are put forward to help facilitate related studies in the future.
Keywords: Environmental education -- Curricula -- South Africa; Conservation of natural resources -- South Africa -- Eastern Cape -- Swartkops Nature Reserve; Conservation of natural resources -- South Africa -- Eastern Cape -- Swartkops River